Impact of needle gauge on characterization of endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) histology samples. Issue 5 (3rd April 2014) - Jeyabalan, Abiramy; Shelley‐Fraser, Golda; Medford, Andrew R.L.
Abstract Background and objective Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) is a minimally invasive mediastinal node sampling technique used for lung cancer staging and diagnosis of mediastinal lesions. The four published studies assessing sampling with 21‐G or 22‐G needles conflict. The study objective is to evaluate the diagnostic utility of 21‐G versus 22‐G EBUS‐TBNA needles, and the ability to subcharacterize both benign and malignant lesions using histopathological assessment only. Methods A retrospective analysis was performed from 303 patients referred for EBUS‐TBNA between January 2011 and July 2013. Sampling needle gauge was selected at the discretion of the operator. Samples were assessed by histopathologists blinded to the needle gauge without rapid on‐site evaluation for cytology. Contingency table analysis was performed to compare diagnostic utility and ability to subcharacterize malignant and benign lesions. Results No difference in diagnostic ability was seen for malignancy (96.6% v 95.3% accuracy, 21‐G vs 22‐G). Subgroup analysis of benign 21‐G tissue samples revealed superior characterization compared with 22‐G samples (63/76, 83%, vs 31/52, 60%, P < 0.01). Characterization of non‐small cell lung cancer (NSCLC) was also significantly better with samples obtained with 21‐G needles versus 22‐G needles (57/65, 88% vs 34/52, 65%, P < 0.01). Conclusions This large UK single‐centre study suggests 21‐G EBUS‐TBNA needles are superior to 22‐G in characterizing benign lesions (especially sarcoidosis) and NSCLC when using histopathological assessment. Making a positive benign diagnosis may avoid the need to perform mediastinoscopy. Obtaining sufficient histological material to subcharacterize NSCLC and particularly lung adenocarcinoma allows appropriate testing for genetic mutations facilitating targeted oncological therapy.